Migration in Southeast Asia IMISCOE Regional Reader - Petcharamesree, Sriprapha; Capaldi, Mark P. (IMISCOE Research Series,, 2023)
This open access IMISCOE Regional Reader explores the issues faced by migrant groups in Southeast Asia and the challenges of getting of their human rights recognized. It analyses the different responses, or lack thereof, of the Association of Southeast Asian Nations (ASEAN) to these highly complex situations which are shaped by contemporary debates around borders and concepts of states, migrants' rights as well as access to citizenship and how these concepts and paradigms are intertwined with issues such as agency and resilience of migrants. Crucial attention is given to the region's lesser known populations and issues such as the Vietnamese in Thailand, people of Indonesian descent (PIDs) in Southern Philippines, independent child migrants across the region, and the vulnerabilities of migrant workers facing the COVID-19 pandemic. With its unique regional focus, this book provides a valuable resource to those studying human rights and migration issues, policy makers and researchers and students.